2017
DOI: 10.17533/udea.iee.v35n2a03
|View full text |Cite
|
Sign up to set email alerts
|

Profile of nursing diagnoses in people with hypertension and diabetes

Abstract: Objective. To identify the profile of nursing diagnoses in people with hypertension and diabetes in primary health care. Methods. A cross-sectional study involving 175 individuals followed up in eight primary health units of Minas Gerais, Brazil. Data collection was made through interview and physical examination, and diagnostic inference was made according with NANDA-I Taxonomy II. Results. The average age of the users was 62.1 years and the female gender predominated (66.9%). A total of 26 diagnoses were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 20 publications
3
15
0
10
Order By: Relevance
“…As for insomnia, a study on the profile of nursing diagnoses in patients with hypertension and diabetes showed that insomnia was present in 51.4% of the sample (Castro-Sampaio et al, 2017). In addition, difficulty in maintaining sleep in diabetic patients may mean more than fatigue, since it interferes directly with metabolic control, production of glucocorticoids, and glucose levels (Cunha, Zanetti, & Hass, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for insomnia, a study on the profile of nursing diagnoses in patients with hypertension and diabetes showed that insomnia was present in 51.4% of the sample (Castro-Sampaio et al, 2017). In addition, difficulty in maintaining sleep in diabetic patients may mean more than fatigue, since it interferes directly with metabolic control, production of glucocorticoids, and glucose levels (Cunha, Zanetti, & Hass, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the complications of unstable blood glucose level in patients with DM, it is necessary to identify risk factors for unstable blood glucose and to develop preventive measures. Nurses, working in different scenarios and health care levels (primary, secondary, and tertiary), play a leading role in the implementation of systematic nursing care with a focus on preventing complications of chronic diseases, and above all, in the pursuit of patient adherence to diabetes management plan that is necessary to an effective glycemic control (Castro-Sampaio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…O outro diagnóstico relacionado ao ganho de peso do paciente é o DE estilo de vida sedentário (pertencente ao Domínio Promoção da Saúde) o que reafirma que o sedentarismo associado à alimentação inadequada e o aumento de peso na população mundial têm contribuído com o acréscimo no número de casos de DM, principalmente o tipo 2 21,25 . Neste sentido, o enfermeiro deve incentivar modificações do estilo de vida em pessoas em condições crônicas, com ações de promoção da saúde como práticas saudáveis de alimentação e realização de atividade física regular, que possam contribuir para a melhoria dos indicadores de controle clínicos da DM 10,25 . O DE risco de glicemia instável também foi identificado [19][20][21][22][23][24][25][26]28 , sendo este um dos principais diagnósticos de enfermagem a ser considerado no paciente diabético a fim de evitar as complicações decorrentes das alterações glicêmicas.…”
Section: Discussionunclassified
“…Neste sentido, o enfermeiro deve incentivar modificações do estilo de vida em pessoas em condições crônicas, com ações de promoção da saúde como práticas saudáveis de alimentação e realização de atividade física regular, que possam contribuir para a melhoria dos indicadores de controle clínicos da DM 10,25 . O DE risco de glicemia instável também foi identificado [19][20][21][22][23][24][25][26]28 , sendo este um dos principais diagnósticos de enfermagem a ser considerado no paciente diabético a fim de evitar as complicações decorrentes das alterações glicêmicas. Em relação aos fatores de risco de glicemia instável foram encontrados: alterações nos níveis de hemoglobina glicada, índice de massa corpórea >31 Kg/m 2 , história prévia de hipoglicemia, déficit cognitivo/demência, neuropatia autonômica cardiovascular, comorbidades e perda de peso que correspondem a fatores de risco descritos na taxonomia NANDA-I 4,29 .…”
Section: Discussionunclassified
See 1 more Smart Citation